'Being Invisible, They Seemed Dead Already': Afterlives of the Dead Wife in A Passage to India. (19th October 2022) - Hashmi, Sania Iqbal
Abstract: Gail Minault has argued that the absence of Muslim women from colonial narratives on India is typically attributed to the women's veiling practices. The colonizers contended that they couldn't possibly write about that which they could not see. We find resonances of that outlook in E. M. Forster's A Passage to India, which, as this article will argue, is constructed upon and around the narrative invisibilization of Muslim women in general, and Dr Aziz's dead wife in particular. Through a close reading of the dead wife's photographic and mnemonic trace in the novel, the article shall observe how her character (or the lack thereof) emerges as the grounds upon which Aziz's relationship is defined with the English characters. It shall then take cognisance of the dead wife's invisibilization beyond Forster, and examine how and why her story has hitherto escaped serious critical enquiry among postcolonial (and) feminist scholars who have worked extensively on Forster's novel. Even though Indian feminist (and) post-colonial theory has presented to us a nuanced understanding of women's subalternity at the hands of the white and the brown man, there appears to be a widespread essentialization at play, which absorbs the lived realities of non-Hindu and non-upper caste women. With sole focus on the figure of the Indian Muslim woman in the project of decolonization, this article will examine how the principles and structures of invisibilization are perpetuated from the logic of colonial bondage to the myth of post-colonial freedom(s).